Development of method for simultaneous measurement of gross alpha and beta in aqueous environmental samples / Masitah Alias - Alias, Masitah (Institute of Graduate Studies, UiTM, 2014)
Measurement of gross alpha and beta in aqeous environmental sample using standard method is a very lengthy, tedious and time consuming process. Alternatively, liquid scintillation counting (LSC) offers a better solution, since the latest model of LSC offer simultaneous counting of gross alpha and beta. The success of LSC technique will depend on two factors; first is the proper setting of the LSC window and its pulse shape analyzer (PSA) concluded in the new protocol for alpha beta simultaneous counting. Secondly, the successful incorporation of the water phase which contains the radionuclides into the organic solvent phase using proper choice of emulsifier which produce a clear stable solution with reasonably high counting rate and figure of merit.